2018
DOI: 10.1021/acsanm.8b01731
|View full text |Cite
|
Sign up to set email alerts
|

π-Conjugated Amine–ZnO Nanohybrids for the Selective Detection of CO2 Gas at Room Temperature

Abstract: The development of a new type of hybrid material comprising naphthalene-based π-conjugated amine (NBA) and zinc oxide (ZnO) nanohybrid, grown in situ on polydimethylsiloxane (PDMS) flexible substrate, is explored. The morphology of the nanohybrids is controlled by optimizing growth time of the hydrothermal reaction. The CO 2 sensor utilizing NBA−ZnO nanohybrids shows outstanding sensing performance with a maximum response of ∼9% to 500 ppm of CO 2 at room temperature and a comparatively fast response/recovery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 62 publications
(78 reference statements)
2
21
0
Order By: Relevance
“…This further increases the resistance of the AmG/PANI sensor in the presence of CO 2 . 25,41 Thus, the enhanced CO 2 sensing properties of the AmG/PANI nanober sensor can be attributed to the presence of the primary amine functional group and the p-n junction between p-type PANI and n-type AmG.…”
Section: Gas Sensing Properties Of Amg/pani Nanober Compositesmentioning
confidence: 99%
See 2 more Smart Citations
“…This further increases the resistance of the AmG/PANI sensor in the presence of CO 2 . 25,41 Thus, the enhanced CO 2 sensing properties of the AmG/PANI nanober sensor can be attributed to the presence of the primary amine functional group and the p-n junction between p-type PANI and n-type AmG.…”
Section: Gas Sensing Properties Of Amg/pani Nanober Compositesmentioning
confidence: 99%
“…24-26 CO 2 is a hard acid and can efficiently interact with the amino groups, which are hard bases, to form carbamates or bicarbonates, resulting in an increase in resistance. 24,25 In this work, we used ethylenediamine [NH 2 -(CH 2 ) 2 -NH 2 ] to functionalize the graphene surfaces, similar to in our previous work. 27 Many studies have demonstrated that primary amine groups are highly efficient in adsorbing CO 2 gas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Novel materials, such as amino-ZnO [ 13 ], Ru@WS 2 [ 14 ], vanadium oxide [ 15 ], nanodiamonds [ 16 ], Al/maPsi/n-Si/Al [ 17 ], and carbon nanotube [ 18 ], have been recently explored for CO 2 gas sensing at room temperature. However, the sensing thin films of these materials require a mild thermal treatment before the sensing at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…CO 2 sensors are widely used in many applications such as air-quality monitoring, food packaging, greenhouse-gas monitoring, medical diagnosis, re detection, and consumer electronics. [1][2][3] Another crucial requirement for monitoring the level of CO 2 is found inside the greenhouse, where the growth of plants is directly dependent on the CO 2 concentration. Therefore, regulation and monitoring of the CO 2 level is also important in the agriculture industry.…”
Section: Introductionmentioning
confidence: 99%